PENGARUH TAWAS PADA PENCELUPAN BAHAN KATUN MENGGUNAKAN ZAT WARNA ALAM EKSTRAK DAUN PETAI CINA (Leucaena Leucocephala) - YULIANTI YULIANTI; yusmar emmy katin; rahmiati rahmiati (Journal of Home Economics and Tourism, 2013)
Abstract This research describes the color, value and flatness color produced in cottondyeing using a banana leaf extract Mordant china with alum concentration of 10grams, 30 grams, 50 grams. This type of research is a quasi experimental researchdesign. The research consisted of two variables, namely, variable X is used in cottondyeing extracts banana leaf china and Y variables are the result of immersion includecolor (hue), dark bright color (value) and the flatness of color. The type of data is theprimary data. Data sources amounted to 15 people consisting of five faculty membersdressmaking KK subjects and 10 subjects dressmaking students. The data isprocessed using analysis of variance (ANOVA) one-way, with SPSS version 12.0.The results are significant differences due to the influence of the concentration ofalum 10 grams, 30 grams, 50 grams to cotton using leaf extract petai china. As forthe flatness of color there is no significant difference due to the effect of alumconcentration of 10 grams, 30 grams and 50 grams. Kata kunci : Pengaruh tawas, Pencelupan katun, Ekstrak Daun Petai Cina